Changes in T-cell subsets and clonal repertoire during chemoimmunotherapy with pembrolizumab and paclitaxel or capecitabine for metastatic triple-negative breast cancer. Issue 1 (27th January 2022) - Chun, Brie; Pucilowska, Joanna; Chang, ShuChing; Kim, Isaac; Nikitin, Benjamin; Koguchi, Yoshinobu; Redmond, William L; Bernard, Brady; Rajamanickam, Venkatesh; Polaske, Nathan; Fields, Paul A; Conrad, Valerie; et al.
Abstract : Background: Chemoimmunotherapy is a standard treatment for triple-negative breast cancer (TNBC), however, the impacts of different chemotherapies on T-cell populations, which could correlate with clinical activity, are not known. Quantifying T-cell populations with flow cytometry and T-cell receptor (TCR) immunosequencing may improve our understanding of how chemoimmunotherapy affects T-cell subsets, and to what extent clonal shifts occur during treatment. TCR immunosequencing of intratumoral T cells may facilitate the identification and monitoring of putatively tumor-reactive T-cell clones within the blood. Methods: Blood and tumor biopsies were collected from patients with metastatic TNBC enrolled in a phase Ib clinical trial of first or second-line pembrolizumab with paclitaxel or capecitabine. Using identical biospecimen processing protocols, blood samples from a cohort of patients treated for early-stage breast cancer were obtained for comparison. Treatment-related immunological changes in peripheral blood and intratumoral T cells were characterized using flow cytometry and TCR immunosequencing. Clonal proliferation rates of T cells were compared based on intratumoral enrichment. Results: When combined with pembrolizumab, paclitaxel and capecitabine resulted in similar time-dependent lymphodepletions across measured peripheral T-cell subsets. Their effects were more modest than that observed following curative-intent dose-dense anthracycline and cyclophosphamide (ddAC) (average fold-change in CD3 + cells, capecitabine: −0.42, paclitaxel: −0.56, ddAC: −1.21). No differences in T-cell clonality or richness were observed following capecitabine or paclitaxel-based treatments. Regression modeling identified differences in the emergence of novel T-cell clones that were not detected at baseline (odds compared with ddAC, capecitabine: 0.292, paclitaxel: 0.652). Pembrolizumab with paclitaxel or capecitabine expanded T-cell clones within tumors; however, these clones did not always expand within the blood. Proliferation rates within the blood were similar between clones that were enriched and those that were not enriched within tumors. Conclusion: Chemoimmunotherapy for metastatic TNBC with pembrolizumab and capecitabine or paclitaxel resulted in similar peripheral T-cell subset lymphodepletion without altering T-cell clonal diversity. Regression modeling methods are applicable in immune monitoring studies, such as this to identify the odds of novel T-cell clones emerging during treatment, and proliferation rates of tumor-enriched T-cell clones.